Proceso de atención de enfermería en paciente masculino de 30 años de edad con neumonía grave asociada a VIH. - Toapanta Herrera, Amarilys Lisley (2020)
HIV is an epidemic of our time, it is very easy to get sick, the dissemination must be made known to the public to take extreme measures. Minimize prevention and health or risk behaviors. Because there is no vaccine for this disease, there is no cure and it can be life threatening. Mastering professional nursing training is essential. Take care of the process and identify problems and needs of the patient to carry out clearly corresponding procedures. Take care and propose alternative solutions; in this way, it helps improve user service in all services. The research was carried out using bibliographic sources on different topics. For a clear and specific concept, and also to help understand the cause and to take the correct care procedures. The interview. For the nursing professional it is very important to apply the nursing care process which will help us to carry out a systematic and organized method in order to provide individualized care to each person, applying skills, abilities acquired correctly since each patient responds in a manner different before an alteration either real or potential. The general objective in this clinical case is to apply the nursing care process in a male patient with severe pneumonia associated with HIV.